PENGARUH LEAN MANAGEMENT TERHADAP KINERJA OPERASI DENGAN BUDAYA ORGANISASI SEBAGAI MEDIASI DI FUTONG PORT - Tri Masni Arta Sihaloho; Hardi, Hardi; M. Yusuf (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2025)
This study aims to analyze the effect of Lean Management on operational performance with organizational culture as a mediating variable at Futong Port. Lean Management is implemented to eliminate waste, improve efficiency, and optimize operational processes. However, its implementation is often hindered by an unsupportive organizational culture. This study employs a quantitative method using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine the relationships between Lean Management, organizational culture, and operational performance. The results indicate that Lean Management positively influences operational performance, both directly and through organizational culture as a mediator. A strong and innovation-supporting organizational culture enhances the effectiveness of Lean Management in improving operational efficiency. This study provides insights for port management in adopting more effective operational strategies by considering the role of organizational culture. The practical implications of this study highlight the importance of employee training, technology adoption, and performance measurement based on Lean Management to improve Futong Port’s competitiveness